An exploratory study considering the potential impacts of high-fidelity simulation based education on self-evaluated confidence of non-respiratory physiotherapists providing an on-call respiratory physiotherapy service: a mixed methods study. (30th July 2019) - Mansell, Stephanie K; Harvey, Alex; Thomas, Amanda
Abstract : Introduction: Physiotherapists working on-call to provide emergency respiratory services report stress and lack of confidence in on-call scenarios. Simulation-based education (SBE) is a potential solution to improve confidence and reduce stress of on-call physiotherapists. In physiotherapy, use of SBE is sporadic. The aim of this study was to evaluate the addition of SBE to an on-call training programme on non-respiratory physiotherapists' self-evaluated confidence. Additionally, the study aimed to evaluate if SBE facilitates identification of learning needs. Methods: This cohort study took a mixed methods approach. Participants were recruited from staff providing on-call respiratory physiotherapy services at a UK hospital. Participants received traditional on-call training over 1 year, with SBE added the subsequent year, in a pre-post analysis design. Self-evaluated confidence was assessed with the Association of Chartered Physiotherapists in Respiratory Care Acute Respiratory/On-call Physiotherapy Self-evaluation of Competence (ACPRC) questionnaire. Two focus groups were conducted post-SBE. Results: There were 10 participants. Thematic analysis of focus groups indicated participants found SBE provided coping strategies for on-call working. Using coping strategies taught in SBE reduced stress levels and increased confidence of non-specialist on-call physiotherapists. ACPRC questionnaire scores significantly improved following the addition of SBE (median change 5.5%, p=0.034, r=0.57). SBE assisted in identification of learning needs through recognition of unconscious incompetence and reinforcement of conscious and unconscious competence. Conclusions: SBE may improve self-evaluated confidence of non-specialist on-call physiotherapists. SBE assists in learning needs identification. SBE could enhance training of physiotherapists providing on-call respiratory services. Further larger trials investigating optimal methods of on-call physiotherapy postgraduate education are warranted.